The Effect of Traditional Chinese Mind-Body Exercise (Baduanjin) and Brisk Walking on the Dorsal Attention Network in Older Adults With Mild Cognitive Impairment - Xia, Rui; Qiu, Pingting; Lin, Huiying; Ye, Bingzhao; Wan, Mingyue; Li, Moyi; Tao, Jing; Chen, Lidian; Zheng, Guohua (Frontiers in Psychology, 2019)
A growing number of studies have shown that mind-body exercise is beneficial to cognitive function, especially memory, in elderly MCI patients. However, few studies have explored the effect of mind-body exercise on the attention of MCI population. We recruited 69 participants and divided them equally into Baduanjin, brisk walking exercise or usual physical activity control groups. The two exercise groups performed 60 min of exercise three times per week for 24 weeks. All subjects underwent whole-brain functional MRI and assessment of attentional abilities, including selective, divided, and sustained attention, and processing speed at baseline and after 24 weeks. The results show that: Baduanjin exercise significantly increased the selective attention of MCI patients, and Dorsal attention network of Baduanjin exercise group exhibited functional connectivity decreased in right rolandic operculum (ROL. R) , right middle temporal gyrus (MTG. R) , right supramarginal inferior parietal, angular gyri (IPL. R), right precuneus (PCUN. R) and right fusiform gyrus (FFG. R) regions compared with the other two groups. The brisk walking exercise group had obviously functional connectivity increased in IPL. R and decreased in the MTG. R region compared to that in the usual physical activity group. But no significant association between the changes of functional connectivity of DAN and the change of attentional ability test was observed. Thus, our data indicated Baduanjin exercise may be a potential beneficial intervention to improve the attention of the elderly with MCI. Further study with more samples is necessary to elucidate its imaging mechanism.